Raising the Barriers to Access to Medicines in the Developing World – The Relentless Push for Data Exclusivity. Issue 1 (27th January 2016) - Diependaele, Lisa; Cockbain, Julian; Sterckx, Sigrid
Abstract: Since the adoption of the WTO‐TRIPS Agreement in 1994, there has been significant controversy over the impact of pharmaceutical patent protection on the access to medicines in the developing world. In addition to the market exclusivity provided by patents, the pharmaceutical industry has also sought to further extend their monopolies by advocating the need for additional 'regulatory' protection for new medicines, known as data exclusivity. Data exclusivity limits the use of clinical trial data that need to be submitted to the regulatory authorities before a new drug can enter the market. For a specified period, generic competitors cannot apply for regulatory approval for equivalent drugs relying on the originator's data. As a consequence, data exclusivity lengthens the monopoly for the original drug, impairing the availability of generic drugs. This article illustrates how the pharmaceutical industry has convinced the US and the EU to impose data exclusivity on their trade partners, many of them developing countries. The key arguments formulated by the pharmaceutical industry in favor of adopting data exclusivity and their underlying ethical assumptions are described in this article, analyzed, and found to be unconvincing. Contrary to industry's arguments, it is unlikely that data exclusivity will promote innovation, especially in developing countries. Moreover, the industry's appeal to a property rights claim over clinical test data and the idea that data exclusivity can prevent the generic competitors from 'free‐riding' encounters some important problems: Neither legitimize excluding all others.